Macchine e cicli nella produzione del vino: uno studio comparativo tra Andalusia (Spagna) e Puglia (Italia). - Palomares Alarcón, Sheila (2022)
Andalusia and Apulia, both in the national and international context, are centres that stand out for their important wine production. Over the centuries, they have experienced a gradual and significant development of industrial making process, and, above all, the machinery used in the processes. Around the last quarter of the 19th century, the small, sometimes modestly sized, artisan cellars began to develop into modern wine cellars or wine factories in which, for the development of the production process, the new machines played a fundamental role in the technological evolution and architectural design of the production structures. The aim of this paper is to study the stages in the wine making process and the technological innovation of the machines preserved and exploited inside the historical cellars; moreover, we want to demonstrate - through a comparative study between the two realities (Spanish and Italian) - if there were and are different production systems (cycles, machines, equipment and organisation) to obtain the finished product.